2016
DOI: 10.3390/nu8120782
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Compound Chrysin Inhibits Retinal Neovascularization with Abnormal Capillaries in db/db Mice

Abstract: Diabetic retinopathy (DR) develops in a significant proportion of patients with chronic diabetes, characterized by retinal macular edema and abnormal retinal vessel outgrowth leading to vision loss. Chrysin, a naturally-occurring flavonoid found in herb and honeycomb, has anti-inflammatory, antioxidant, and anti-cancer properties. This study sought to determine the protective effects of chrysin on retinal neovascularization with abnormal vessels and blood-retinal barrier (BRB) breakdown in 33 mM glucose-expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 45 publications
(100 reference statements)
1
23
0
Order By: Relevance
“…This study found that the treatment with micromolar chrysin reduced mesangial fibrosis through inhibiting collagen deposition and α-SMA induction in glucose-stimulated mesangial cells and in PAS-positive diabetic kidneys. Several studies have shown renorotection of chrysin in experimental animal models [ 30 , 40 , 41 , 42 , 43 ]. Our previous study revealed that chrysin dampened diabetes-associated renal tubulointerstitial fibrosis through inhibiting epithelial to mesenchymal transition [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study found that the treatment with micromolar chrysin reduced mesangial fibrosis through inhibiting collagen deposition and α-SMA induction in glucose-stimulated mesangial cells and in PAS-positive diabetic kidneys. Several studies have shown renorotection of chrysin in experimental animal models [ 30 , 40 , 41 , 42 , 43 ]. Our previous study revealed that chrysin dampened diabetes-associated renal tubulointerstitial fibrosis through inhibiting epithelial to mesenchymal transition [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study shows that serum angiopoietin-2 may be a potential predictor of acute pancreatitis severity and an indicator of renal dysfunction in the development of acute pancreatitis-renal syndrome [ 47 ]. Although this study did not monitor the serum angiopoietin-2 after chrysin treatment to diabetic mice, our previous study showed that oral administration of chrysin diminished the tissue level of angiopoietin-2 in diabetic mouse retina [ 30 ]. It was assumed that chrysin could modulate vessel outgrowth and sprouting leading to the promotion of angiogenesis and vasculogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following intake by humans, chrysin has low oral bioavailability and rapid fecal elimination, in which its major form in plasma is chrysin sulphate [ 28 , 30 ]. Our previous study showed that the multifunctional chrysin exerted the retinoprotection through inhibiting diabetes-associated retinal neovascularization and blood–retinal barrier breakdown [ 31 ]. However, whether chrysin is capable of preventing vision loss in diabetic ocular diseases remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, mRNA of tumor necrosis factor in vitreous body of patients and its expression of soluble receptors increased significantly. The animal research indicated that used angiogenin-1 could control the expression of tumor necrosis factor effectively, which was helpful to improve the prognosis of early diabetic retinopathy in rats [22][23][24].…”
Section: Discussionmentioning
confidence: 99%